Correlation between gymnastics elements knowledge and performance success in younger categories of alpine skiing - Lesnik, B.; Glinsek, V.; Zvan, M. (Science of Gymnastics Journal, 2015)
On a sample of 24 female competitors and 30 male competitors (ages 12 to 13 years) we wished to determine the correlation between knowledge of gymnastic elements and acrobatics, and performance success in Mercator Cup children's competitions in alpine skiing. The sample of variables at the measurements consisted of evaluations of eight (8) gymnastic and acrobatic skills (evaluated on scale 0-5), while performance success criterion was represented by competitors ranking in the official children's competitions in ski season 2013/14.By means of calculating the Spearman coefficient of correlation (rs), we found that by female competitors two individual gymnastics variables, as well as average evaluations of all gymnastics variables are statistically significantly associated with the performance success criterion. Based on the processing of data by the method of using the "Mann Whitney U test," we both in girls (GIM; Sig. =0.012*) as well as in boys (GIM; Sig.=0.033*) confirmed a statistically significant correlation between the average values of gymnastics variables (GIM) and the performance success in competitions in the Mercator Cup. This means that both in boys as well as in girls higher rankings in competitions were achieved by those with better knowledge of acrobatics and gymnastics elements.